MiR‐496 promotes migration and epithelial‐mesenchymal transition by targeting RASSF6 in colorectal cancer. Issue 2 (4th July 2019) - Wang, Hua; Yan, Bianbian; Zhang, Pan; Liu, Shuzhen; Li, Qiqi; Yang, Jin; Yang, Fangfang; Chen, Erfei
Abstract: Aberrant loss of tumor‐suppressor genes plays a crucial role in tumorigenesis and development of colorectal cancer (CRC). Extensive studies have reported tha hypermethylation of Ras association domain family member 6 (RASSF6) is common in various solid tumors. Another important mode of epigenetic regulation, microRNA (miRNA) regulation of RASSF6, is far from clear. The aim of the present work was to screen out novel miRNA regulating RASSF6, and to explore its underlying mechanism in CRC. With the use of bioinformatics, clinical sample data, and luciferase binding assay, we determined that microRNA‐496 (miR‐496) could be a novel oncomiR that directly binds to RASSF6. Next, a series of miR‐496 mimics or inhibitor, or RASSF6 small interfering RNA (siRNA) introduced into CRC cells were applied to examine the effect of miR‐496 on CRC cell viability, migration, and epithelial‐mesenchymal transition (EMT). The results demonstrated that miR‐496/RASSF6 could promote cell migration and EMT via Wnt signaling activation, but had no effect on cell viability. Our results confirmed that the miR‐496/RASSF6 axis is involved in Wnt pathway‐mediated tumor metastasis, highlighting its potential as a therapeutic target for CRC. Abstract : The key findings demonstrated the miR‐496/RASSF6 axis is involved in Wnt pathway‐mediated tumor metastasis, highlighting its potential as a therapeutic target for colorectal cancer.